Stone induced ureteral rupture: The worst-case scenario. A case report - Fares Kosseifi (Urology Case Reports, 2021)
Forniceal rupture secondary to acute ureteral obstruction is relatively common. However, spontaneous ureteral rupture is less frequently encountered. Most reported cases were stone related, localized at the ureteropelvic junction and managed in a minimally invasive manner. We present a case of stone induced ureteral rupture below the UPJ, with bacterial and fungal superinfections, that failed conservative management and lead eventually to nephrectomy. No such scenario has ever been reported in the literature. As rupture of the ureter can cause serious complications, including urinoma, sepsis and sometimes kidney loss, prompt recognition, treatment and follow-up of the condition is therefore necessary.